2018
DOI: 10.7752/jpes.2018.01015
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The objective of this exploratory study was to identify the content of preservice teachers' practical knowledge and the influence of their acculturation experiences on their practical knowledge. Informed by teacher occupational socialisation theory, a mixed method design was used to examine 26 first-year preservice physical education and health (PEH) teachers' practical knowledge construction during their first PEH course. Data collection included a written assignment in which the preservice teachers, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…If we compare the findings on activity habits with national surveys on the content of physical education in Norway, we see a correlation where the content of physical education is largely ball games and basic training [58]. Furthermore, this picture may coincide with the findings of Curtner-Smith [5], González-Calvo and Gerdin [9] and Romar and Åström [7], which showed that interest in sport and physical activity was the main motivator for many in the choice to start studies to become PE teachers. The question is whether these interests that the students have will also make them prioritise this type of activity in their future teaching, as suggested in the study by González-Calvo and Gerdin [9].…”
Section: Findings and Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…If we compare the findings on activity habits with national surveys on the content of physical education in Norway, we see a correlation where the content of physical education is largely ball games and basic training [58]. Furthermore, this picture may coincide with the findings of Curtner-Smith [5], González-Calvo and Gerdin [9] and Romar and Åström [7], which showed that interest in sport and physical activity was the main motivator for many in the choice to start studies to become PE teachers. The question is whether these interests that the students have will also make them prioritise this type of activity in their future teaching, as suggested in the study by González-Calvo and Gerdin [9].…”
Section: Findings and Discussionmentioning
confidence: 63%
“…Interest in sport and physical activity turns out to be the main motive for many who want to start studies to become PE teachers [5,6]. In Sweden, Romar and Åström [7] found that students starting PETE had largely positive experiences as students in the subject and that they had a great interest in sports and physical activity. These findings reflect results from studies in England [8].…”
Section: Introductionmentioning
confidence: 99%